Nieuwenhuistensor of almost complex structure - Ahmed Thamer Abd Ali; Ufuk Öztürk; A. A. Shihab (Genius Journals, 2022)
In this work, complex structures are considered, we build two bases: RA -basis and A - basis. We also define an almost complex structure and its adjointG -structure. We define locally the Nijenhuis tensor of an almost complex structure, prove that this tensor is defined globally, and obtain an explicit expression for this tensor.
Keywords: Adjointg -structure; complex structure; almost complex structure; Nijenhuis tensor